Flipped classroom pedagogy: Using pre-class videos in an undergraduate business information systems management course. Issue 6 (8th July 2019) - Das, Ashish; Lam, Tri Khai; Thomas, Susan; Richardson, Joan; Kam, Booi Hon; Lau, Kwok Hung; Nkhoma, Mathews Zanda
Abstract : Purpose: The purpose of this paper is to illustrate the implementation of the flipped classroom method in teaching the course and to investigate the student's perceived helpfulness, learning outcomes and satisfaction in respect of the pre-class learning videos. Design/methodology/approach: Pre-class learning videos were integrated into a course to encourage students to acquire knowledge before lectures and workshops. Having completed the flipped classroom, a delivery questionnaire containing all items was distributed to all of the participants. The data collected were analysed statistically, using a structured equation modelling technique. Findings: Findings indicate that the perceived quality of experience of using videos before lectures and workshops has a positive influence on the perceived helpfulness of the pre-class learning videos. Furthermore, the perceived helpfulness of the pre-class learning videos has a positive effect of the acquisition perceived learning outcomes. The perceived helpfulness of the pre-class learning videos also has a positive impact on the student satisfaction with the course. Finally, there is a positive and causal relationship between the perceived learning outcomes and student's satisfaction with the course. Originality/value: Analysis reveals that the learning process and student satisfaction are improved by using pre-class learning videos.